DIALEKTIKA PETANI DALAM MEMILIH MELAKUKAN PERTANIAN ORGANIK (Fenomena Romantisme Pertanian Di Wilayah Ganjuran, Kabupaten Bantul) - , RIZKA KHOIRULIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Farming involution which is symptomed by disappearance of farming culture triggers romanticism feeling among farmers. These conditions lead struggle within the farmers, so that farmers in some of Ganjuran areas chose to develop organic farming. Every farmer has different understanding on organic farming, as well as dialectical process. In Karl Marx thought, human dialectics do have a relationship with materialism element captured through human sense. Dialectics brought a new consciousness in viewing organic farming as contradiction and interrelation which later form its consciousness. From these results, it was known that some farmers made sense of independence organic farming by exploiting the potential of natural resources in the region. For some other farmers, organic farming was defined as a market opportunity, so that organic farming was limited only for results achievement without considering the principle of independence. The type of this research was analitical descriptive field research. Data collection method was conducted qualitatively through observation, interview, and documentation.